TRANSFORMASI DIGITAL DALAM PENDIDIKAN: TANTANGAN DAN PELUANG MENUJU PEMBELAJARAN DI ERA DIGITAL - Dadang; Karep (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Transformation digital transformation in education is an important step in the era of globalization and rapid technological rapid technological advancement. The application of technology in the learning process teaching and learning process, including the use of digital devices and online platforms, aims to improve the accessibility, efficiency and quality of education. Methods The research method used in this article is Library Research, which collecting information from various literature sources to explore the issue of digital transformation. digital transformation. The results show that although digital transformation offers opportunities for more interactive and innovative learning, challenges such as the digital divide and lack of training for teachers must be overcome. teachers must be addressed. Recommended strategies include infrastructure development infrastructure development, training for educators, and integration of data-driven learning. With these measures, it is hoped that all students will be able to make the most of technology, thereby improving the quality of education. to the fullest, thus improving the overall quality of education.